2017
DOI: 10.1080/20009666.2017.1379852
|View full text |Cite
|
Sign up to set email alerts
|

Use of dictation as a tool to decrease documentation errors in electronic health records

Abstract: Background: Use of Electronic Health Records is increasing. Copy-and-paste function is frequently used with higher rates of documentation errors. Studies to determine the nature of such errors are needed.Objectives: Determination of the effect of implementing a dictation system for completing notes on the quality of clinical documentation. We hypothesized that implementation of the dictation system for note writing would decrease the rate of errors in the progress notes as well as decrease the rate of copying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…On the other hand, one of the disadvantages attributed to the EHR is that it allows "copy & paste" of previous records, duplicating information and perpetuating possible errors. This functionality has appeared in the literature related to saving time, increasing the efficiency of the process (Al Hadidi et al, 2017;Hartzband and Groopman, 2008;Heiman et al, 2014;Hirschtick, 2006;March et al, 2016;Shoolin et al, 2013). Transcriptions should be made in a conscious and responsible way by health professionals, taking advantage of the positive points for which "copy & paste" was created.…”
Section: Phrs Compared To Ehrsmentioning
confidence: 99%
“…On the other hand, one of the disadvantages attributed to the EHR is that it allows "copy & paste" of previous records, duplicating information and perpetuating possible errors. This functionality has appeared in the literature related to saving time, increasing the efficiency of the process (Al Hadidi et al, 2017;Hartzband and Groopman, 2008;Heiman et al, 2014;Hirschtick, 2006;March et al, 2016;Shoolin et al, 2013). Transcriptions should be made in a conscious and responsible way by health professionals, taking advantage of the positive points for which "copy & paste" was created.…”
Section: Phrs Compared To Ehrsmentioning
confidence: 99%
“…Notably, use of dictation technology has been associated with decreased use of Copy/Paste functionalities and decreased documentation errors. 28 Prior work has demonstrated a reduction in users of speech recognition technology after initial adoption to a more stable core set of users, corresponding with a "trough of disillusionment" in the adoption of new technologies. 29 This suggests that the learning curve associated with use of voice recognition technologies could be a focus for technological innovation and training.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalists were found to prefer in-person interactions with consults instead of over-the-phone consults or pages due to a higher level of productive communication, reducing turnaround time by up to 50% [17][18][19]. When documenting, dictating notes resulted in increased coherence due to an improvement in the quality of information due to a decrease in errors [20]. Multiple studies have shown that these systems increase satisfaction and efficiency positively, while decreasing overall monthly medical transcription cost [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…When documenting, dictating notes resulted in increased coherence due to an improvement in the quality of information due to a decrease in errors [20]. Multiple studies have shown that these systems increase satisfaction and efficiency positively, while decreasing overall monthly medical transcription cost [20,21]. Another form of dictation is through a voice-recognition app on a smartphone that allows hospitalists to create notes quickly or record a voice file that can later be used as a progress note [22].…”
Section: Introductionmentioning
confidence: 99%